Crítica da racionalidade ambiental ao regime de exploração do petróleo no Brasil a partir da carência de gestão democrática participativa - Xavier, Osmar Caetano (2020)
This dissertation aims as object of study the social participation in the legal, political and economic petroleum exploration regime. The research's relevance is in the fact that there are no indications that the locacions affected by petroleum are in increasing human development, despite being a natural richness of great commercial value and contained in abundance in Brazil. Despite its exploitation in Brazil pointing to economic growth, what is observed is the promotion of environmental degradation, social exclusion and regional inequality, beyond to commune to unitary market sign through the hypereconomization of the world. Petroleum has a 13% share in the Brazilian Gross Domestic Product (GDP) and there is the prospect that Petrobras Company will produce daily approximately 4.2 million of petroleum barrels of great commercial value in 2020. However, under this regime, there is no reversal of economic benefits in improving the living conditions in the impacted communities and the social participation of this population at is not taken account, which is why its questioned if there is a relationship between the absence of participatory democratic management and the ineffectiveness of the oil company exploitation regime in Brazil? From this problematization, the research's objective is to analyze the historical and material constraints in which the petroleum legal regulation is inserted, to identify if there are legal, economic and political inconsistencies in the current petroleum exploration regime and to analyze the viability of a new petroleum exploration regime based on the participatory democratic management of energy wealth from petroleum. Enrique Leff's environmental rationality will adopted as a method, from self-management as a form manifestation of political power. This method allows to unbuild the power strategies of the rationality of market combining the theoretical and instrumental order of knowledge with the riverside communities values, rural communities and from working masses and urban peripheries which constitute the environmental knowledge. It opens the way for a new rationality to a intercultural and integrated base of the knowledge, to encompass the questions of the appropriation of natural resources with dialogicities outside the capitalist market. From the environmental rationality, whose results indicate the opening of space to dialogue with civil society, respecting the authority and the recognition of the plurality of the development, it try to extract data, mostly qualitative, from books, scientific journals and positive law regulations pertaining to the petroleum exploration regime, social participation and environmental rationality. These data provided the elements to verify the hypothesis: from the point of view of the impacted communities, the petroleum exploration regime can not be effectived because there is deficiency participatory democratic management that incorporates the interests of these sectors.